Social Media Marketing and Repurchase Intentions in Sharia Hotels: The Mediating Influence of Brand Awareness - RASYIDDIN, AHMAD; Hurriyati, Ratih; Dirgantari, Puspo Dewi; Mac-Doqu, Francis Kortey (Yayasan Sinergi Kawula Muda, 2026)
The Islamic hospitality industry faces a tough challenge in maintaining repurchase intentions amid increasingly fierce competition. Although social media marketing activities (SMMAs) have become the dominant strategy, the psychological mechanisms that explain the conversion of these activities into repetitive buying behaviors are still not optimally internalized; This is reflected in the empirical paradox in which increased digital investment successfully attracts new visitors, but fails to prevent a drastic decline in retention rates. This causal explanatory research aims to analyze the role of brand awareness (BA) mediation in the relationship between SMMA and buyback intention (RI) in the context of Islamic boarding houses, as well as validate relevant theoretical frameworks. Using the Partial Smallest Square Structural Equation Modeling (PLS-SEM) on a sample of 98 respondents who are actual customers of Islamic boarding schools in West Java, the results of the study prove that SMMA has a significant effect on the Republic of Indonesia, both directly and indirectly through the mediation of BA. In particular, Brand Awareness has been shown to act as a significant partial mediation mechanism, while also confirming the Stimulus-Organism-Response (S-O-R) Framework in the sharia hospitality market. These findings provide crucial practical implications for sharia lodging managers to shift the focus of their social media content strategy: optimizing efforts that consistently build brand recall and brand recognition instead of simply pursuing reach metrics), thus being able to transform brand awareness into continuous repeat buying behavior.